Kilka uwag na temat związków państwa, prawa i administracji - Kusiak-Winter, Renata (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
Relations between state, law and administration are of a complex nature and have been observed from the historical and comparative perspective. The essence of the relations should be analyzed regarding its impact on the society and the rights of the individual citizen.
Keywords: administrative law; public administration; state